1986
DOI: 10.1002/em.2860080204
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multiple parameters of rodent carcinogenicity and in vitro genetic toxicity

Abstract: The relationship between chemically induced patterns of tumorigenesis in rodents and of in vitro genetic toxicity was evaluated for 73 substances. tumorigenicity patterns were defined according to sex and species effects, the induction of common or uncommon tumors, and benign or malignant tumors. These results and the genetic toxicity results derived from the testing of chemicals under code were compared. Chemicals that induced tumors in both sexes of both rodent species (trans-sex/species carcinogens) were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Recently, Ashby and Tennant, expanding upon and corrobor ating the work ofTennant et al (154), found that the distribution of tumor sites for agents mutagenic to Salmonella is different from those which are not (76). They examined 222 carcinogens which had been tested by the NCI/NTP in both mice and rats.…”
Section: Genotoxic Versus Nongenotoxic Agents and The Rodent Bioassaymentioning
confidence: 94%
“…Recently, Ashby and Tennant, expanding upon and corrobor ating the work ofTennant et al (154), found that the distribution of tumor sites for agents mutagenic to Salmonella is different from those which are not (76). They examined 222 carcinogens which had been tested by the NCI/NTP in both mice and rats.…”
Section: Genotoxic Versus Nongenotoxic Agents and The Rodent Bioassaymentioning
confidence: 94%
“…In TA1537 and TA100, mutagenicity was also found without metabolic activation [14]. The metabolite, N-acetyl-4,4'-oxydianiline, was mutagenic in the presence of S9 mix in the strains TA98 and TA100; N,N'-diacetyl-4,4'-oxydianiline was not mutagenic [2].…”
Section: Genotoxicitymentioning
confidence: 97%
“…In L5178Y mouse lymphoma cells, 4,4'-oxydianiline (concentrations not specified) was mutagenic with and without S9 mix [14,16]. In another L5178Y mouse lymphoma test, positive results were obtained without metabolic activation with 4,4'-oxydianiline concentrations from 50 to about 250 µ g/ml.…”
Section: Genotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…According to TemaNord, no evidence for genotoxicity was found in a wide range of in vitro studies, such as Salmonella/microsome test, mouse lymphoma TK +/-assay, chromosome aberration/sister chromatid exchange test in Chinese hamster ovary cells, and rat hepatocyte/DNA repair assay (no further details on any of these studies were given) (Ashby et al, 1988;Benigni, 1989;Cameron et al, 1987;Gulati et al, 1989;Kornbrust and Barfknecht, 1985;McGregor et al, 1988;Mortelmans et al, 1986;Shelby and Stasiewics, 1984;Sweeney et al, 1994;Tennant et al, 1986Tennant et al, , 1987Zeiger, 1987).…”
Section: Genotoxicitymentioning
confidence: 99%